Histone H4-based peptoids are inhibitors of protein arginine methyltransferase 1 (PRMT1). Issue 16 (21st August 2020) - Mann, Sarah A.; DeMart, Megan K.; May, Braidy; Causey, Corey P.; Knuckley, Bryan
Abstract : Methylation of arginine residues occurs on a number of protein substrates, most notably the N-terminal tails of histones, and is catalyzed by a family of enzymes called the protein arginine methyltransferases (PRMTs). This modification can lead to transcriptional activation or repression of cancer-related genes. To date, a number of inhibitors, based on natural peptide substrates, have been developed for the PRMT family of enzymes. However, because peptides are easily degraded in vivo, the utility of these inhibitors as potential therapeutics is limited. The use of peptoids, which are peptide mimetics where the amino acid side chain is attached to the nitrogen in the amide backbone instead of the α-carbon, may circumvent the problems associated with peptide degradation. Given the structural similarities, peptoid scaffolds may provide enhanced stability, while preserving the mechanism of action. Herein, we have identified that peptoids based on natural peptide substrates are not catalyzed to the product by PRMT1, but instead are inhibitors of this enzyme. Reducing the length of the peptoid reduces inhibition and suggest the residues distal from the site of modification are important for binding. Furthermore, a positive charge on the N-terminus helps promote binding and improves inhibition. Selectivity among family members is likely possible based on inhibition being moderately selective for PRMT1 over PRMT5 and provides a scaffold that can be used to develop pharmaceuticals against this class of enzymes.